FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SOP RUMAH SAKIT DENGAN SITUASI PANDEMIK YANG MENYEBABKAN KECEMASAN PASIEN YANG AKAN DIRAWAT - Nanda Gumilang; Bela Purnama Dewi (LPPM STIKes Mitra Adiguna, 2022)
Corona virus (Corona virus Disease, Covid-19) is a type of disease that infects the respiratory system and has no known etiology. The purpose of the study was to determine the factors related to hospital SOPs with pandemic situations that caused anxiety in patients who would be treated at Siti Fatimah Hospital Palembang in 2022. The research method used was quantitative analytic with a cross-sectional approach. The population in this study were all patients who will be treated at Siti Fatimah Hospital, South Sumatra Province with a total sample of 35 respondents who were taken using the accidental sampling method. The results showed that the frequency distribution of most respondents experienced anxiety as many as 19 respondents (54.3%), most of the respondents had less knowledge as many as 20 respondents (57.1%). The results of statistical tests showed that there was a relationship between knowledge (p.value = 0.012) and disease history (p.value = 0.033) with the anxiety level of patients who would be treated at Siti Fatimah Hospital Palembang in 2022. Suggestions are expected to provide information or counseling to patients who will hospitalization regarding Covid-19 problems and procedures that must be followed by patients before being treated in accordance with hospital SOPs using language that is easily understood by patients so that it is expected to reduce the patient's level of anxiety before being hospitalized in the hospital.